Performance of graphene oxide and coconut shell activated carbon for 131i isolation from delay tank - Hadzuan, Fara Hana Mohd (2023)
Iodine-131, with a half-life of 8 days and about 971 keV excess energy, is the well-known radionuclide used for hyperthyroidism and thyroid cancer. Due to its considered low-medium half-life, differentiated thyroid cancer (DTC) patients administered with high energy 131I need to be isolated until at least minimal radiation exposure is achieved. An underground system known as a delay tank is used to withhold the 131I and other clinical wastewater until a non-hazardous level is achieved and discharged into the main sewage system. The Nuclear Medicine Department, HUSM has only two isolation wards for the DTC patients and the delay tank of the department has a limited capacity hence linked to the restriction of patients’ admissions. Thus, an alternative technique using graphene oxide (GO) and coconut shell activated carbon (CSAC) was proposed for isolating the 131I clinical wastewater from the delay tank. The synthesized GO and CSAC were mixed with radioactive clinical wastewater with varying concentrations and filtered using membrane filter paper to collect the sediment. The decay rate of 5 mg/mL for both carbon-based materials was significantly higher than the concentrations 1, 2, 3, and 4 mg/mL, which indicates active interaction has occurred. The synthesized carbonbased materials, along with the sediments, were analyzed in several characterization studies; via Field Emission Scanning Electron Microscopy (FESEM), GO and CSAC were found appeared wrinkled-like tissue and had micropores on the surface, respectively; X-ray Diffraction (XRD) of GO, GO:131I, CSAC and CSAC:131I obtained 2-theta (